2017
DOI: 10.1089/jpm.2016.0313
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the “Surprise” Question in Predicting Survival among Older Patients with Acute Surgical Conditions

Abstract: The surprise question is a valuable tool for identifying older patients with higher risk of death, and it may be a useful screening criterion for older emergency general surgery patients who would benefit from palliative care evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 24 publications
1
33
2
1
Order By: Relevance
“…’) is a method used when considering whether someone may benefit from palliative care. 37 Hostel staff and healthcare professionals indicated that for many homeless people, the answer to this question would be ‘no’. Their health is often poor, and their needs are complex making it hard to identify who might be considered palliative.…”
Section: Resultsmentioning
confidence: 99%
“…’) is a method used when considering whether someone may benefit from palliative care. 37 Hostel staff and healthcare professionals indicated that for many homeless people, the answer to this question would be ‘no’. Their health is often poor, and their needs are complex making it hard to identify who might be considered palliative.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies had insufficient data to be included in the meta-analysis. Three authors responded to requests, but were unable to provide additional data to that presented in the paper [ 37 , 39 ]. One author was not contactable [ 38 ].…”
Section: Studies With Incomplete Datamentioning
confidence: 99%
“…The actual survival figures were not reported [ 36 ]. Lilley et al [ 39 ] reported on the accuracy of 28 clinicians who provided responses for 163 patients. Their results show a ‘No’ SQ response was given in 93 cases (60%).…”
Section: Studies With Incomplete Datamentioning
confidence: 99%
See 1 more Smart Citation
“…We recently completed a systematic search and analysis. We searched for "surprise question" in five electronic databases (MEDLINE, Embase, PsycINFO, Cochrane Library and CINAHL) and identified two additional full papers (Lilley and colleagues, and Gómez-Batiste and colleagues) 2,3 with values of 82.2% and 93.7% for sensitivity, and 48.7% and 26.4% for specificity, respectively. Downar and colleagues 1 included six published abstracts; we believe that these should be considered with caution, because results can change following peer (including statistical) review.…”
mentioning
confidence: 99%